Adapting Education to the Development of Post-Industrial Processes in an Economy: Extra-Curricular Project-based Learning for Developing the Innovative Abilities of High School and University Students (London Journal of Research In Management & Business, 2023)
The post-industrial orientation of an economy towards professionals capable of developing and implementing innovative solutions determines the need for rethinking the goals of education and changing educational technologies.Based on the analysis of the distributions of statistical indicators characterizing changes in national education systems in connection with the development of the economy, steady trends in the  growth of the population's level of education and the duration of the higher education cycle, which goes beyond competitive expediency, are shown.At the same time, the trends of increasing educational loads and informational saturation of education can be alleviated by modern opportunities for extra-curricular forms of education that are compatible with business activity and career development of a specialist.